Peningkatan Literasi Sains Siswa Menggunakan Model Project Based Learning berbantuan Metode Eksperimen Pada pelajaran Fisika Kelas X Fase E - Tanjung, Sastika; Hidayati, Hidayati; Hasmita, Gustuti (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Students at SMAN 1 Ulakan Tapakis have low scientific literacy, which prompted this study. Based on the results of the PISA study, the scientific literacy of Indonesian students is still relatively low because the results obtained have not reached the OECD average score of 485. This type of research is quantitative research involving all students of class X of SMAN 1 Ulakan Tapakis in the 2023/2024 academic year. Sampling was carried out using purposive sampling. The sample in this study, namely class X.E1, was taken based on consideration of the results of daily tests. Several factors that are the basis for selecting students in the class are interviews as one of the research methods used in data collection and direct observation in the school field. The results of the simple water wheel experiment carried out by students with infographics containing the process or steps of the experiment and the working principles of the experiment carried out, can run according to the images displayed in the results and discussion sections. The results of the study showed that there was an increase in students' daily test scores after making a project using the experimental method. On average, students obtained daily test scores above the KKM, which was 75. However, there were still students who obtained low scores because the simple water wheel project they made had not been implemented properly